2001
DOI: 10.1007/s002100000344
|View full text |Cite
|
Sign up to set email alerts
|

Inositolphosphate formation in thoracic and abdominal rat aorta following G q/11 -coupled receptor stimulation

Abstract: Although thoracic and abdominal rat aorta are often used as a classical pharmacological preparation for the assessment of vascular drug effects, little is known on regional differences among these two parts of the aorta with regard to their reaction to Gq/11-coupled receptor activation. Thus, we determined, in rings from thoracic and abdominal aorta from 12-week-old male Wistar rats, the effects of noradrenaline (NA; 10(-8)-10(-4) M), endothelin-1 (ET-1; 10(-10)-10(-6) M) and the thromboxane A2 mimetic U 46619… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…From these experiments pK B -values for 5-MU were calculated ranging from 7.2 to 7.5 which are between its affinity at α 1A -(8.63; Michel et al 1995) and α 1B -and α 1D -adrenoceptors (6.97 and 7.31; Michel et al 1995). Involvement of α 1D -adrenoceptors seems to be unlikely because BMY 7378 exhibited only at the rather high concentrations of 3×10 -7 M and 10 -6 M antagonistic effects against NA-induced contraction with pK B -values of 7.0-7.4 which are by far lower than the affinity of BMY 7378 at the α 1D -adrenoceptor (8.2-9.4; Dhein et al 2001). On the other hand, CEC (30 µM, i.e.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…From these experiments pK B -values for 5-MU were calculated ranging from 7.2 to 7.5 which are between its affinity at α 1A -(8.63; Michel et al 1995) and α 1B -and α 1D -adrenoceptors (6.97 and 7.31; Michel et al 1995). Involvement of α 1D -adrenoceptors seems to be unlikely because BMY 7378 exhibited only at the rather high concentrations of 3×10 -7 M and 10 -6 M antagonistic effects against NA-induced contraction with pK B -values of 7.0-7.4 which are by far lower than the affinity of BMY 7378 at the α 1D -adrenoceptor (8.2-9.4; Dhein et al 2001). On the other hand, CEC (30 µM, i.e.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, neither prazosin (10 -9 -10 -7 M) nor the α 1A -adrenoceptor-selective antagonist 5-MU (10 -8 M and 10 -7 M) nor the α 1D -adrenoceptor-selective antagonist BMY 7378 (10 -7 M and 10 -6 M) exhibited considerable antagonistic activity against NA-induced contraction although they were used in concentrations 10-to 100-fold higher than their affinities at α 1 -(prazosin pK B 8.5-10; Starke 1981; Hieble et al 1995;Alexander and Peters 1999), α 1A -(5-MU pK B 8.63; Michel et al 1995) or α 1D -adrenoceptors (BMY pK B 8.2-9.4; Dhein et al 2001). Accordingly, a significant contribution of α 1A -or α 1D -adrenoceptors to the contractile action of NA in human saphenous vein is quite unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the question of the identity of the α 1 -adrenoceptor subtype mediating constriction in the rat thoracic aorta (e.g. Dhein et al 2001;Hussain and Marshall 1997;Xu and Han 1996). It is now generally accepted that the primary receptor subtype involved is the α 1D -adrenoceptor; however, effects via α 1A -and α 1B -adrenoceptors have also been demonstrated (Testa et al 1995;Fagura et al 1997;Villalobos-Molina and Ibarra 1996).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that ET-1 caused [ 3 H]IP formation in rat thoracic and abdominal aorta via stimulation of ET A receptors (Dhein et al 2001). In the present study in rings of thoracic aorta obtained from AOB rats ET-1-induced [ 3 H]IP formation was at all three time points measured (i.e.…”
Section: Aortamentioning
confidence: 96%